Kecerdasan Artifisial dan Perencanaan Pendidikan dalam Konteks Kurikulum Merdeka di Indonesia - Ine Masruroh, Sri (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to analyze the controversy that has emerged around the implementation of the Independent Curriculum in Indonesia, focusing on the debate between national standardization efforts and meeting local needs in the midst of the era of disruption. The research approach used is a qualitative approach with case studies in several schools in urban and rural areas. Data were collected through participant observation, in-depth interviews with teachers, principals, students, and parents, and studies of curriculum documents and education policies. The analysis uses the interactive 3 models of Miles and Huberman. The results of the study indicate tension between the demands of curriculum uniformity to achieve national standards and the need for curriculum flexibility that is adjusted to the local context. Differences in school capacity, resource availability, and student characteristics in various regions are the main factors that trigger the controversy. This study contributes to a deeper understanding of the challenges of implementing the Independent Curriculum and offers recommendations for solutions to overcome the gap between national standardization and local needs, so that it can improve the quality of education in Indonesia evenly